Effect of Applying the E-Learning Learning Model as a Solution to the Covid-19 Pandemic on Student Learning Outcomes - Jainal Abidin; Agustina Siburian (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
The process of development of science and technology in this era is growing rapidly. This is in line with the times, we are faced with a world problem, namely the COVID-19 pandemic which requires us to comply with health protocols and avoid crowds to reduce the process of spreading the covid-19 virus. The effect of implementing these regulations resulted in the teaching and learning process that should have been carried out face to face to become network-based learning. The use of E-learning media is expected to overcome learning limitations due to the covid-19 pandemic. So, when conducting research it was found that learning with E-learning media had not been able to provide satisfactory results on student learning outcomes, where student learning outcomes did not reach the target KKM value = 75. Many factors influenced this including not all students who have smartphones and low network signal quality.